Sea Toll: A Way to Save The Economic of East Indonesia Through East Java - Mohammad Ammar Alwandi; Dewi Widyawati; Siti Muchlisoh (East Java Economic Journal, 2020)
East Java is part of the international global supply chain and the gateway of trade to eastern Indonesia. East Java became the center of trade links to East Indonesia where this connection was strengthened by Tol Laut which is a subsidized cruise to and from Eastern Indonesia. The Covid-19 pandemic that infected East Java led to a decrease in people’s purchasing power and caused the trade sector to contract. This economic contraction caused shock in supply and demand. This research aims to explore the potential of East Java to rebound from economic contraction due to the Covid-19 pandemic. The analysis methods used are descriptive analysis and inference analysis using the panel’s spatial regression analysis method. As a result of this study, Tol Laut is a solution to resurrect and save the economy in Eastern Indonesia by lowering transportation costs thus refueling interregional trade.